Telaah Ringkas Tafsir Abul A'la Al Mawdudi, Tafhim Al Qur'an - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (The International Journal of Pegon : Islam Nusantara civilization, 2025)
The paper investigates the principle of tafsir espoused by Abul A‘la al-Mawdudi (1903-1979) in his seminal work, Tafhim al-Quran (Towards Understanding the Qur’an). The work shows a balanced approaches between tafsir bil ma’thur (narrative commentary) and tafsir bil ra’y (independent judgement) developed in his interpretation. The study is of descriptive-qualitative type in the form of literature review and content analysis. It critically examines the text of Tafhim al-Quran (Towards Understanding the Qur’an), its content, themes, relational ideas, style and doctrine. The finding shows that al-Maududi had succinctly applied concise ways in explaining the verse that largely derived from classical authoritative sources. It reflected a balance approach of traditional and modern ideal brought forth in his tafsir that illustrates its puritanical and argumentative nature underlying his interpretation that brings original and in-depth discussion of the text. Makalah ini mengkaji corak dan prinsip tafsir yang dibawa oleh Abul A‘la al-Maududi (1903-1979) dalam magnum opus-nya kitab Tafhīm al-Qur’an. Ia memperlihatkan kaedah yang seimbang antara pendekatan tafsir al-ma‘thur (berasaskan riwayat) dan al-ra’y (penalaran dan logika) yang diterapkan dalam penafsirannya. Metode kajian ini bersifat deskriptif-kualitatif (naratif) dari jenis tinjauan pustaka dan analisis isi. Ia mengkaji teks kitab Tafhim al-Qur’an dan meneliti kandungan dan tema-tema asas tentang manhaj, hubungan idea dan doktrin tafsir yang dikembangkannya. Temuan kajian mendapati al-Maududi menerapkan analisis yang ringkas dalam penjelasan ayat yang digarap dari sumber-sumber tradisional yang autoritatif. Tafsirnya mengimbangi pendapat-pendapat klasik dan moden dalam penakwilan hukum dan fiqh dan membawa idealisme tafsirnya yang puritan yang dikembangkan dalam perbincangan teksnya yang mendalam.